RANCANG BANGUN SISTEM INFORMASI PENGGAJIAN PT. SEKAR CAHAYA TEKNIK CIKARANG - - Universitas Bina Sarana Informatika, Yahya Mara Ardi; - STMIK Nusa Mandiri, Syafrianto (APMMI - Asosiasi Profesi Multimedia Indonesia, 2021)
ABSTRACT - Salary is a direct compensation given to employees as remuneration for the work that has been done. The payment of employee salaries must be carried out professionally with the aim of creating a good reciprocal relationship between the agency and the employee. This is intended so that the implementation of rights and obligations can be carried out in harmony and balance. PT Sekar Cahaya Teknik is a company engaged in the field of Trading and Fabrication which is still processing data manually. The process of entering and processing data is done in a semi-manual way, namely using Microsoft Excel, and employee payroll still uses a manual method, namely by using salary slips as evidence. With a system that is still manual, of course it is not effective. 2 So the data processing takes a long time. In addition, it is possible for errors to occur in the implementation of data processing which ultimately results in information that is not timely, inaccurate, and does not match what is needed. From the problems above, it is necessary to create an integrated computer-based system to help ease the management task. In this case, especially for employee payroll. Therefore, there was an impetus for compiling a study entitled